PENERAPAN PETA KONSEP (CONCEPT MAPPING) DAN BADAN DIKOTOMI KONSEP (BDK) SERTA PENGARUHNYA TERHADAP PENGUASAAN KONSEP SISWA DI MA AL-FATAH PALEMBANG - Jhon Riswanda; Dini Afriansyah (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2018)
The purpose of this study was to look at the effect of Concept Maps and BDK on circulatory system material in humans on the mastery of student concepts based on the Bloom Tax Revision C1-C6. Methodology is an experimental Quasy which compares between two methods. The results showed that there were significant differences between before and after treatment with Concept Maps and BDK with average N -Gain being 0.31 for Concept Maps and 0.41 for BDK, where in all categories showed a significant increase after treatment, except C6. This result shows that concept maps and BDK are highly recommended as a method especially mastery of student concepts approach to mastering learning outcomes, recommended for originating from the Koran, which is highly application in the field.